Analysis of the Health of Sharia Banks with Approach to Rentability Factors (Earning) - Tri Kurniawati, E; Hadi, S; Harventy, G; Syaifullah, Y (KnE Social Sciences, 2019)
The level of health of Islamic banks is a measure that States that an Islamic banking institutions have good qualifications in terms of liquidity, solvency and profitabiltias, in addition to being able to run the function and role of intermediary institutions as well. This research aims to analyze the extent of the influence of the ratio of the supporting factors in the assessment of earning or earning ratios that in proxy by the Return On Asset (ROA) as the variable X 1, the ratio Retun on Equity (ROE) as the variable X 2 and the ratio of Assets that can generate revenue (IGA) as the variable X3 in contributing the main factor ratio rentabiltias at the level of health of bank syariah i.e. Net Operating Margin (NOM) as the variable Y. The sample in this research is the entire population of the study i.e. the National Islamic Bank which has provided a bank statement on the financial services authority (OJK) for the period January 2013 until December 2017. Model analysis of the multiple linear regression model using and being estimated using OLS (Ordinary Least Square). Based on the research results obtained value R Square of 0,406. The figure indicated that the ability of the independent variable (the ratio of ROA, ROE ratio and the ratio of IGA) in explaining his independe variables (ratio of NOM) amounted to 40.6% while the rest is affected by other variables. Keywords: bank, earning health levels, return on assets, return on equity, the ratio of assets that can generate income, net operating margin